On Export and Economic Growth: A Comparative Analysis of Selected West African Countries - Oluwatobi, Adekunle Ahmed; Daniel, Gbadebo Adedeji; Akande , Joseph Olorunfemi (International Journal of Economics and Financial Issues, 2022)
The effect of export on economic growth has attracted much attention amongst researchers and practitioners. Conventional theories posit that output growth is attainable if countries produce and export the goods in which they have comparative advantages or are resourcefully endowed. Available evidence, however, sometimes present negative or inconclusive results on export-growth nexus. The study applied the panel cointegration and panel corrected standard errors (PCSE) on a sample of thirteen selected West African countries for the period 1990-2018. The result shows existence of cointegration amongst the variables. The PCSE results indicate positive long run relationships between export and growth, on one hand and exchange rate and growth, on the other. The study recommends measures to improve trade and attain growth in region such as the complete removal all forms of export restrictions and tariff on primary products, as well as administrative tax exemptions for domestic firms that engage in production of export goods.